Al-Qur’an, Gaya Hidup Halal, dan Fusion Of Horizons: Studi QS. Al-Baqarah (2): 168 - Irawati Irawati; Mohammad Ithof (IAIN Madura, 2020)
The rapid development of modern era and technology has been motivated Muslim(s) to deepen their Islamic knowledge and faith, covering how they select foods, outfits, and economic transactions model. This phenomenon has led to a new term namely Halal Lifestyle and so that became a basis for this article. The trend of halal lifestyle in this disruption era was used as an opportunity by businessmen or investors, both local and foreign, to promote their syaria-branding business. The primary root of this paper is the existence of al-Qur'an as a holy book, which contains various things of human problems, including about the halal way of life. We refered to the hermeneutic theory “fusion of horizon” initiated by H.G. Gadamer by harmonizing historical texts of the past and history of the present. This theory was used to correlate between Al-Qur’an, al-Baqarah (2): 168 and the halal lifestyle trend in the current era of disruption.